Clonal variation in a four year old plantation of Triplochiton scleroxylon K. Schum. and its relation to the predictive test for branching habit - Ladipo, D.O.; Leakey, R.R.B.; Grace, J. (1991)
Considerable clonal variation is reported in the size and form of the West African tree TripZochiton scleroxyZon K. SCHUM after four years of growth in plantations near Ibadan, Nigeria. At normal spacing (2.4 m) mean heights ranged from 5.9 m to 8.1 m, whilst at wide spacing (4.9 m) the range was 5.1 m to 7.8 m, although the trunks had a greater diameter. Form varied considerably, some clones having straight monopodial stems while others were multi-stemmed, much-forked or heavily branched. The relationship between these characteristics and the result of a Predicitive Test for Branching Habit is reported. This test is based on genetic variiation in apical dominance following decapitation and is made on very young plants in the nursery, 3 to 4 weeks after removal of the terminal bud. There were correlations between field characters (extent of branching, the incidence of heavy branching, and the diameter of the stem) and indices obtained from the test. The possibility is discussed of using the test to screen young seedlings for those which, following vegetative propagation, are likely to give clones with a low branching frequency and high harvest index.